32. NUTRITIONAL STATUS IN ORAL CAVITY CANCER PATIENTS RECEIVING CONCURRENT CHEMORADIATION THERAPY (Vietnam Journal of Community Medicine, 2025)
Objective: Description of certain clinical and nutritional characteristics of patients with oral cavity cancer undergoing concurrent chemoradiotherapy at Nghe An Oncology Hospital from January 2024 to September 2024.Subjects and Methods: This is a descriptive, prospective cohort study involving 40 oral cancer patients receiving chemoradiotherapy. Data was collected through interviews, medical records, and assessment of weight before and after treatment.Results: The weight loss rate was 57.5%, with an average weight loss of 4 ± 1.5 kg. The weight loss rate was higher in patients aged ≥ 60 years (64%), female patients (62.5%), and especially in those with a BMI ≥ 23 kg/m² before treatment (82.4%). Patients with periodontitis (83.3%), in stages III–IV of the disease (67.7%), and not receiving tube feeding (72.7%) also had a higher rate of weight loss. Treatment toxicity symptoms contributing to increased weight loss included grade III oral mucositis (76.9%), dysphagia (70.8%), xerostomia (69%), nausea/vomiting (76.9%), trismus (80%), fatigue (60%), anorexia (60%), and gastrointestinal disturbances (53.8%).Conclusion: Weight loss is a common issue in oral cancer patients undergoing chemoradiotherapy, particularly in those overweight before treatment. Regular weight monitoring and early nutritional intervention are essential to mitigate the negative impact of weight loss on treatment outcomes and patients' quality of life.
Keywords: Weight loss; oral cancer; chemoradiotherapy; quality of life